FATWA EKONOMI SYARIAH DI INDONESIA - Marwing, Anita (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
This article aims to review the fatwa concerning sharia economics in Indonesia which includes the method and process of establishing a fatwa on sharia economics and fatwa on sharia economics issued by the National Sharia Council of the Indonesian Ulema Council. This institution has the duty to explore, study, formulate the values and principles of Islamic law (syariah) to be used as guidelines in transaction activities in Islamic financial institutions, as well as oversee their implementation and implementation. This guideline is then poured in the form of fatwa by paying attention to the general welfare and maqashid syari'ah so that the fatwa can truly answer the problems that arise in the community and can truly be an alternative that can be used as a guide in running a sharia economic business in Indonesia.